Impact of ICT Pedagogical Practices of B.Ed. Student-Teachers on Learning Outcomes - Kalpana, K.; Kumawat, B.C. (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
It is a known fact that every field is touched by ICT. The use of ICT is rapidly increasing in our Indian society viz, Business, Hospital, Shopping mall. The reason behind its development is none other than the Education. Our Indian educational system has implemented ICT in every standard of learning to know the basics of computer and use the concept of E-learning. E-learning resource is a global network where learning could be done in online and offline and it is considered as a solution for a problem of delivering the resources required and to facilitate the lifelong learning and we believe that sometimes learning outcomes focus on the results of learning experiences where the teacher and the students get an opportunity of using various methods and techniques by different applications available on the internet.